NUMERICAL CALCULATION OF ZEEMAN EFFECT AND LANDE-FACTOR IN NANOWIRE GATED QUANTUM DOTS - BOUDIB, OUAHIBA; MIMOUNE, SOURI MOHAMED (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
A self-consistent solution of the Poisson-Schrodinger equations in gated quantum dot is performed using the control volume method to give the spin states of electrons and the Zeeman splitting energy. In this work, we have calculated the Landé g- factor in several orientations of the external magnetic field. We have also studied the influential related coefficients. Moreover, the variation of potential energy in nanowire quantum dot versus the variation of the voltage gates has been studied. The Results obtained by the present study were in good agreement with those of numerical and experimental methods.